2020
DOI: 10.1007/s11612-020-00523-z
|View full text |Cite
|
Sign up to set email alerts
|

Introducing service robotics in inpatient geriatric care—a qualitative systematic review from a human resources perspective

Abstract: This article in the journal Gruppe. Interaktion. Organisation. (GIO) presents a qualitative systematic review of nursing home staff perspectives on the usage of robotic devices in geriatric nursing. Robotic devices have been introduced to the field of inpatient geriatric care only recently. Although the elderly are seen as the primary users of many robotic devices in geriatric care, staff members are the driving force in the implementation and application of these devices. Hence, the Human Resources department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These terms needed to occur together with at least one of the indicators of successful HRI (i.e., satisfaction , workload , performance , trust , cooperation , acceptanc e, and situation awareness ). This was supplemented with a manual search of reference lists of reviews in the general context of HRI (e.g., Dautenhahn, 2015; Griffin et al, 2017; Hancock et al, 2011; Haubold et al, 2020; Li, 2015; Moran et al, 2015; Murphy, 2004). This yielded a total of 3,398 articles.…”
Section: Methodsmentioning
confidence: 99%
“…These terms needed to occur together with at least one of the indicators of successful HRI (i.e., satisfaction , workload , performance , trust , cooperation , acceptanc e, and situation awareness ). This was supplemented with a manual search of reference lists of reviews in the general context of HRI (e.g., Dautenhahn, 2015; Griffin et al, 2017; Hancock et al, 2011; Haubold et al, 2020; Li, 2015; Moran et al, 2015; Murphy, 2004). This yielded a total of 3,398 articles.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the model contains factors influencing the use of robots as well as design dimensions. Moreover, residents of a care facility have not been interviewed directly, the studies put their emphasis on the employees-a review has shown that they are not deeply involved often (Haubold et al 2020). Finally, future research needs to evaluate the coding scheme to ensure reliability and validity.…”
Section: Limitations and Implications For Further Researchmentioning
confidence: 99%
“…As shown in Figure 2, the significance of talent evaluation can be seen from it. Although the domestic talent evaluation career has entered a stage of successful development, compared with foreign countries, the domestic talent evaluation is still in its infancy [16].…”
Section: Problems Existing In the Current Talent Evaluationmentioning
confidence: 99%